1998
DOI: 10.1152/ajpcell.1998.275.4.c1081
|View full text |Cite
|
Sign up to set email alerts
|

A role for MAP kinase in differentiated smooth muscle contraction evoked by α-adrenoceptor stimulation

Abstract: The purpose of this study was to investigate the potential role of mitogen-activated protein (MAP) kinase in smooth muscle contraction by monitoring MAP kinase activation, caldesmon phosphorylation, and contractile force during agonist stimulation. Isometric tension in response to KCl and phenylephrine (PE) was measured from strips of ferret aorta. MAP kinase activation was monitored by Western blot using a phosphospecific p44/p42 MAP kinase antibody. Caldesmon phosphorylation was assessed using specific phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
159
4
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(177 citation statements)
references
References 23 publications
(40 reference statements)
13
159
4
1
Order By: Relevance
“…After activation, ERK undergoes a second redistribution to the contractile filament to meet up with its substrate, CaD [Khalil et al, 1995]. ERK-mediated phosphorylation of CaD is known to dis-inhibit actomyosin interactions in vascular muscle [Dessy et al, 1998] and in vitro [Foster et al, 2004]. In the present study we found that a similar translocation of ERK from the cytosol to the surface membrane occurs in late pregnancy in myometrial cells (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…After activation, ERK undergoes a second redistribution to the contractile filament to meet up with its substrate, CaD [Khalil et al, 1995]. ERK-mediated phosphorylation of CaD is known to dis-inhibit actomyosin interactions in vascular muscle [Dessy et al, 1998] and in vitro [Foster et al, 2004]. In the present study we found that a similar translocation of ERK from the cytosol to the surface membrane occurs in late pregnancy in myometrial cells (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…However, as described above, the PE-induced contraction at constant [Ca 2ϩ ] i is thought to result in alleviation of the inhibitory effect of C-terminal caldesmon on actin-activated myosin ATPase activity, possibly by phosphorylation of the C-terminal of caldesmon by MAPK (35)(36) (Fig. 10B).…”
mentioning
confidence: 74%
“…3B1). We have previously shown that ferret portal vein and aortic cells contract in response to PE at near resting [Ca 2ϩ ] i levels in the absence of changes in LC 20 phosphorylation, and this contraction is associated with activation of protein kinase C and mitogen-activated protein kinase (MAPK) and phosphorylation of the C-terminal half of caldesmon (29,(33)(34)(35)(36). In contrast, it is known that microcystin-LR is an inhibitor of myosin light chain phosphatase that causes contraction by increasing LC 20 phosphorylation levels (37).…”
Section: Pe and Microcystin-lr Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, puri®ed caldesmon is phosphorylated by ERK-2 in a cell-free system and addition of ERK-2 to Triton X-100-permeabilized canine airways smooth muscle ®bres potentiates Ca 2+ -induced tension development (Gerthoer et al, 1997). Third, caldesmon is phosphorylated in intact airways, gastrointestinal and vascular smooth muscle during agonist-induced contraction (Dessy et al, 1998;Gerthoer et al, 1996;Gerthoer & Pohl, 1994) at proline-directed serines (i.e. S 789 PTKV and S 759 PAPK), which is characteristic of a mitogen-activated protein (MAP) kinase consensus sequence (Adam & Hathaway, 1993).…”
Section: Introductionmentioning
confidence: 99%